EFEKTIVITAS LAYANAN INFORMASI DALAM MENANGGULANGI PERILAKU MENYIMPANG SISWA SMP NEGERI 1 TELUKDALAM - Kaminudin Telaumbanua (Institut Pendidikan Tapanuli Selatan, 2020)
This research is motivated by the increasing deviant behavior of students such as laziness to learn, taking lessons, fights between students, making noise in class, students are lazy to do assignments, lazy at school, not disciplined, fighting teachers, like to say dirty words, smoking, stealing. . One of the factors that influence students' deviant behavior is the lack of information service provision. The purpose of this research is. 1) Describe the level of deviant behavior of class VIII students before being provided with information services. 2) Describe the level of deviant behavior of class VIII students after being provided with information services. 3) Testing the effectiveness of information services in overcoming student deviant behavior. The research method used is pre-experimental research, namely one group pretest-postest design. Population and research sample of class VIII students of SMP Negeri 1 Telukdalam. Based on the research results obtained. 1) Students' deviant behavior before being given treatment is in the high category with a percentage of 79.49% and an average score of 135.3. 2) The deviant behavior of students after being provided with information services is in the low category with a percentage of 42.91% and an average score of 72.95. 3) Information services can have an effect in overcoming student deviant behavior. Based on the calculation of Zhitung = 4.10, N = 22 and a = 0.05. This means that H0 is rejected and Ha is accepted. It can be concluded that information services are effective in overcoming student deviant behavior because students can be well controlled and under adult supervision, in addition to providing information services based on the topic of problems experienced by students. Suggestions offered by researchers, the principal should provide a special counseling room, in order to support every activity given by the counseling counselor, BK services should be held in the classroom and outside the classroom because counseling in the classroom and outside the classroom is an integral part of professional services in the field. guidance.